Faktor determinan perilaku remaja putri dalam mengatasi dismenore di sekolah MTs - Nuryatna, Dedih (UKInstitute, 2024)
These determinant include knowledge, attitudes, family support, anxiety and behavior of adolescent girls coping with dysmenorrhea. The purpose of this study was to determine the predictor factors of adolescent girls' behavior in overcoming dysmenorrhea in MTs Al-Jauharotunnaqiyah Buah Gede, Serang Regency in 2023. The research method used was cross sectional with a sample of 75 respondents using total sampling. The results of the study almost most (52.0%) showed high knowledge, (54.7%) showed unfavorable attitudes, (56.0%) showed supportive family support, (53.3%) showed no anxiety and (50.7%) showed good behavior. There is no relationship between knowledge and adolescent girls' behavior in overcoming dysmenorrhea in MTs Al-Jauharotunnaqiyah Buah Gede, Serang Regency (p = 0.175). There was no relationship between attitudes and behavior of adolescent girls in overcoming dysmenorrhea in MTs Al-Jauharotunnaqiyah Buah Gede, Serang Regency (p = 0.734). There is a relationship between family support and adolescent girls' behavior in overcoming dysmenorrhea in MTs Al-Jauharotunnaqiyah Buah Gede, Serang Regency (p = 0.017). There is a relationship between anxiety and adolescent girls' behavior in overcoming dysmenorrhea in MTs Al-Jauharotunnaqiyah Buah Gede, Serang Regency (p = 0.021). The factor most associated with adolescent girls' behavior in overcoming dysmenorrhea was family support (p = 0.045). It takes efforts to provide motivation and exposure to media information about dysmenorrhea to improve behavior in overcoming dysmenorrhea.